2010
DOI: 10.1590/s0085-56262010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Insects associated with the composting process of solid urban waste separated at the source

Abstract: Insects associated with the composting process of solid urban waste separated at the source ABSTRACT. Insects associated with the composting process of solid urban waste separated at the source. Sarcosaprophagous macroinvertebrates (earthworms, termites and a number of Diptera larvae) enhance changes in the physical and chemical properties of organic matter during degradation and stabilization processes in composting, causing a decrease in the molecular weights of compounds. This activity makes these organisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 29 publications
(17 reference statements)
0
27
0
1
Order By: Relevance
“…Using two nutrient profiling models developed to combat over-and undernutrition, Payne et al (2015) concluded that insects' contribution to health is not significantly lower than that of meat products, and can actually be significantly higher. Besides their potential contribution to dietary nutrient intakes, thus improving health, insects are also important for improving and conserving the environment as well as contributing to incomes and livelihoods (Morales and Wolff 2010;Ferraro and Andreatta 2014;Halloran and Vantomme 2014). However, more research and documentation are needed on their nutritional values in order to more efficiently promote insects as healthy food (Van Huis et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Using two nutrient profiling models developed to combat over-and undernutrition, Payne et al (2015) concluded that insects' contribution to health is not significantly lower than that of meat products, and can actually be significantly higher. Besides their potential contribution to dietary nutrient intakes, thus improving health, insects are also important for improving and conserving the environment as well as contributing to incomes and livelihoods (Morales and Wolff 2010;Ferraro and Andreatta 2014;Halloran and Vantomme 2014). However, more research and documentation are needed on their nutritional values in order to more efficiently promote insects as healthy food (Van Huis et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Eight 'waves' of worms have been well-known, and each wave assaults deceased animals in a severe series as decay develops from newly deceased carcass through thoroughness and decomposition to mummification. Though several maggots only appear during a noticeably definite stage of animal decomposition, the greedy large maggots of various blow flies nourish on any animal material, comprising living tissues [40].…”
Section: Larvaementioning
confidence: 99%
“…Garbage provide the main medium for breeding. The house fly Musca domestica is usually associated with decomposing substrate of solid urban wastes [9]. Musca domestica are also implicated in the transmission of bacteria such as Salmonella, Shigella, Campylobacter, Escherichia, Enterococus, Chlamydia and many other species that caused illness [7].…”
Section: Introductionmentioning
confidence: 99%